Designed synthesis of FeₓCo₁₀₀₋ₓ alloy nanoparticles by polyol reduction: an evolution of structural, morphological and magnetic properties - Moditma (2022)
FexCo100-x nanoparticles with different stoichiometry (x = 0-100) have been prepared by a facile synthesis process and compositions confirmed using X-ray fluorescence spectroscopy. X-ray diffraction measurements suggest alloy formation in the body-centered cubic (BCC) phase, with a progressive shift of peak positions to account for the stoichiometric changes. The evolution of nanoparticle morphology is from cubic for iron to hexagonal for cobalt, and the entire composition range has been examined. Magnetic behavior has been accessed by Mössbauer spectroscopy and vibrating sample magnetometric measurements, which suggests an increase of magnetization values of iron upon alloying with cobalt. A detailed account of the synthesis scheme has been presented, to achieve uniform alloy nanoparticles in the pristine state with minimum aggregation and surface oxidation, by carefully adjusting the reaction timescales.